Cyanoethyl cellulose‐based eutectogel electrolyte enabling high‐voltage‐tolerant and ion‐conductive solid‐state lithium metal batteries - Hao Zhang; Lixue Zhou; Xiaofan Du; Jianjun Zhang; Songwei Tian; Tingting Liu; Jinning Zhang; Sijia Hu; Weiling Song; Xinhong Zhou; Guanglei Cui (Carbon Energy, 2022)
Abstract Solid‐state polymer electrolytes are an important factor in the deployment of high‐safety and high‐energy‐density solid‐state lithium metal batteries. Nevertheless, use of the traditional polyethylene oxide‐based solid‐state polymer electrolyte is limited due to its inherently low ionic conductivity and narrow electrochemical stability window. Herein, for the first time, we specifically designed a cyanoethyl cellulose‐in‐deep eutectic solvent composite eutectogel as a promising candidate for hybrid solid‐state polymer electrolytes. It is found that the proposed eutectogel electrolyte achieves high ionic conductivity (1.87 × 10−3 S cm−1 at 25°C), superior electrochemical stability (up to 4.8 V), and outstanding lithium plating/striping behavior (low overpotential of 0.04 V at 1 mA cm−2 and 1 mA h cm−2 over 300 h). With the eutectogel‐based solid‐state polymer electrolyte, a 4.45 V LiCoO2/Li metal battery delivers prominent long‐term lifespan (capacity retention of 85% after 200 cycles) and high average Coulombic efficiency (99.5%) under ambient conditions, significantly outperforming the traditional carbonate‐based liquid electrolyte. Our work demonstrates a promising strategy for designing eutectogel‐based solid‐state polymer electrolytes to realize high‐voltage and high‐energy lithium metal batteries.